An Expert Review on the Applicability of Blockly for Industrial Robot Programming - Winterer, Mario; Salomon, Christian; Koberle, Jessica; Ramler, Rudolf; Schittengruber, Markus (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2020)
The paradigm shift triggered by Industry 4.0 leads to a fast rising number of industrial machinery and collaborative robots that increases the need for flexible customization of production processes and automation workflows. End-user programming of industrial robots has become an essential capability for all areas in industry. In this paper, we investigate the applicability of block-based programming languages for large and complex robot programs. Therefore, we implemented a real-world program for industrial robots using Blockly, a block-based visual language, and assessed the results regarding portability, readability, understandability, and maintainability. Our findings are, that (1) large and complex real-world robot programs can be expressed in Blockly, (2) that the readability and understandability of such programs is equal to conventional flow-chart based programming languages, and (3) that the maintainability of Blockly programs can even be considered better than in flowchart based languages. Our results and findings serve as basis for usability studies with end-users in robot programming.